Finding Our Voice: Highly Flexible ED for the HyFlex World - Amy Gagnon; Christina Robinson; Jason A. Melnyk; Jennifer Nicoletti; Kelly McLaughlin; Kristine Larsen; Mina Hussaini (To Improve the Academy)
The COVID-19 pandemic brought about unprecedented changes in our approach to delivering educational development (ED) programming. In this article we discuss how our dual ED centers pivoted during the sudden switch to online learning, highlighting how we overcame challenges such as a small staff, tight timelines, and faculty anxieties. Particularly, we explore how we adapted to the university’s investment in technologically advanced Hybrid-Flexible (HyFlex) classroom spaces and utilized a multi-pronged team approach to provide effective and timely ED to faculty. By identifying key faculty leaders, identifying multiple sources of data, and using multiple modalities, we supported the faculty in their mission to effectively serve their students during this difficult and stressful time. In pivoting from a triage approach to more tactically focused development, the two ED centers discovered that they could more effectively serve faculty (and by extension students) by shattering the structural silos that had previously defined them and instead working as a unified entity.